Demonyms in the «Léxico Mayor de Cuba» (Islas, 2023)
Introduction: The study of demonym adjectives in lexicographical works has gained significance in the 21.st century. The inventory recorded by Esteban Rodríguez Herrera in his Léxico Mayor de Cuba is the most extensive compilation of such units in a Cuban lexicographical work.Methods: All the units included in it were compiled, as the objective is to characterize the inclusion, use and treatment of demonyms in Esteban Rodríguez´s work. They were classified according to their nature, and those that follow the paradigm of «natural of» or «relative to» were selected.Results: General principles of inclusion and organization of terms are not described, so demonym entries vary in terms of structure, quantity, and type of information. The author includes both ancient and currently used demonyms, with diverse territorial scope, although with a preference for the western part of the country. The presence of comments and glosses is irregular.Conclusions: The lexicographical treatment that demonyms receive in the Léxico Mayor de Cuba is not systematic and is influenced by the toponym-demonym relationship, the author's knowledge of geography and history, frequency of usage, and linguistic norms.
Keywords: demonyms; Léxico Mayor de Cuba; Esteban Rodríguez Herrera